Relationship-counselling Recommendations for Partnerships Involving Autistic Adults: A Scoping Review - Andrea Stafford (Psychotherapy and Counselling Journal of Australia)
Romantic relationships involving neurodivergent (ND) adults, in particular a subset where at least one partner in the relationship is autistic, present unique dynamics and challenges regarding partnership communication, emotional connection, intimacy, and engagement. To cater for such relationships, adjustments to relationship therapy may be needed. This scoping review aimed to investigate what is known about relationship-counselling approaches for couples in which an autistic profile has been identified, either through diagnosis or self-identification. A lack of empirical research exploring specific relationship-counselling therapies for ND couples was found; moreover, only two of the nine studies reviewed had qualitatively investigated a specific approach. All studies reached consensus on the need for greater therapist familiarity with autism when working with ND couples. Other common recommendations were to avoid viewing autism as a deficit, to approach ND relationships with a cultural lens to facilitate mutual understanding, and to ensure social support for the neurotypical partner of the relationship. Overall, this review found a need for greater empirical research in ND relationship counselling, including follow-up research to test recommendations.